2020
DOI: 10.1001/jamadermatol.2020.1300
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Risk in Patients Treated With Biologic Therapy for Common Inflammatory Diseases

Abstract: IMPORTANCE Biologic therapies are widely prescribed immunomodulatory agents. There are concerns that compared with treatment with conventional systemic therapy, long-term biologic treatment for common immune-mediated inflammatory diseases, namely inflammatory bowel disease (IBD), rheumatoid arthritis (RA), and psoriasis, may be associated with increased risk of melanoma.OBJECTIVE To examine whether biologic treatment of IBD, RA, or psoriasis is associated with an increased risk of melanoma compared with conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 46 publications
(116 reference statements)
2
29
1
1
Order By: Relevance
“…A study by Esse and collaborators was focused on melanoma risk in patients treated with biologics for common inflammatory diseases, such as inflammatory bowel diseases, rheumatoid arthritis and psoriasis ( 68 ). In detail, they considered a total of 7 studies, consisting of patients treated with TNF-α inhibitors, one of which regarding patients with psoriasis and, moreover, included in our review ( 74 ). According with their findings, the risk of melanoma in biologic-treated patients with IBD and psoriasis compared with their biologic-naïve counterparts receiving conventional systemic therapy showed no statistically significant increases.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Esse and collaborators was focused on melanoma risk in patients treated with biologics for common inflammatory diseases, such as inflammatory bowel diseases, rheumatoid arthritis and psoriasis ( 68 ). In detail, they considered a total of 7 studies, consisting of patients treated with TNF-α inhibitors, one of which regarding patients with psoriasis and, moreover, included in our review ( 74 ). According with their findings, the risk of melanoma in biologic-treated patients with IBD and psoriasis compared with their biologic-naïve counterparts receiving conventional systemic therapy showed no statistically significant increases.…”
Section: Discussionmentioning
confidence: 99%
“…Type ϵ is the only non-immunological AE form, which may be associated with longterm medication. Previous studies (68,69) have shown that excessive release of pathological inflammatory mediators may lead to a high incidence of anxiety and depression; moreover, the application of BAs induces psychologically relevant AEs. The most common type ϵ AE was psychiatric disorder with an incidence of 0.75% (Table S3 and Figure S7.5.1).…”
Section: Discussionmentioning
confidence: 99%
“…24 Other drugs with immunosuppressant actions, commonly used to treat these diseases, are also suggested to increase the melanoma risk. [25][26][27] Furthermore, the propensity of certain immunosuppressants to exacerbate UVR-induced DNA damage is theorized to be responsible for a potential elevated risk of melanoma. 28,29 Corticosteroids, and glucocorticoids in particular, are used as part of a variety of anti-inflammatory and immunosuppressive therapies, for conditions such as rheumatoid arthritis, inflammatory bowel syndrome, psoriasis, and eczema.…”
Section: Introductionmentioning
confidence: 99%